CHARACTERISTICS OF MARINE ENVIRONMENTAL GEOCHEMISTRY FROM NGA SON TO CUA HOI, THANH HOA PROVINCE (0-30 METERS WATER DEPTH) - Huy, Luong Le; Nhuan, Mai Trong; Hoc, Le Van; Tinh, Trinh Nguyen; Thang, Le Anh; Ha, Nguyen Van; Tuan, Hoang Van; Tue, Nguyen Tai; Quy, Tran Dang (Vietnam Journal of Marine Science and Technology, 2017)
The aim of this study is to clarify characteristics of marine environmental geochemistry from Nga Son to Cua Hoi (0-30 m water depth). The water and sediment samples were collected from March to April of each year during the period 2011 - 2013. Results indicated that salinity of seawater ranged from 1.2‰ to 33.3‰. The seawater environment was classified into neutral-weak oxidation in the layer from 0-10 m water depth and weak alkaline-weak oxidation in the layer 10-30 m water depth. Concentrations of most anions and elements in seawater had a decreasing trend from nearshore to offshore regions and with depth, with the exception of SO42-, CO32-, Mg, B-, Br-, I-. Sedimentary environment was highly dominated by neutral-strong oxidization and weak alkaline-weak oxidization for the zone from 0-10 m water depth and 10-30 m water depth, respectively. Concentrations of anions and elements tended to be higher in nearshore region than those in offshore zone, with the exception of SO42-, PO43-, NO3- and positively correlated with fine-grained sediment compositions. Total PCBs concentration increased from north to south, yet HCHs and DDTs had opposite trends. Compared with environmental quality guidelines, marine sediments and seawater were not polluted by heavy metals and organic compounds of PCBs and OCBs.